Genetic transformation of selected mature cork oak (Quercus suber L.) trees. - Alvarez, R.; Alonso, P.; Cortizo, M.; Celestino, C.; Hernández, I.; Toribio, M.; Ordás, R. J. (Plant cell reports, 2004)
A transformation system for selected mature cork oak (Quercus suber L.) trees using Agrobacterium tumefaciens has been established. Embryos obtained from recurrent proliferating embryogenic masses were inoculated with A. tumefaciens strains EHA105, LBA4404 or AGL1 harbouring the plasmid pBINUbiGUSint [carrying the neomycin phosphotransferase II (nptII) and beta-glucuronidase (uidA) genes]. The highest transformation efficiency (4%) was obtained when freshly isolated explants were inoculated with A. tumefaciens strain AGL1. Evidence of stable transgene integration was obtained by PCR for the nptII and uidA genes, Southern blotting and expression of the uidA gene. The transgenic embryos were germinated and successfully transferred to soil.
The following values have no corresponding Zotero field: accession-num: 15185122
Keywords: Agrobacterium; Cork oak; Fagaceae; Somatic embryogenesis; Tree genetic transformation